Age and height predict neuropathy risk in patients with HIV prescribed stavudine - Cherry, C.; Affandi, J.; Imran, D.; Yunihastuti, E.; Smyth, K.; Vanar, S.; Kamarulzaman, A.; Price, Patricia (Lippincott Williams & Wilkins, 2009)
OBJECTIVE: Sensory neuropathy is a common problem in HIV-infected patients and is the dose-limiting toxicity of stavudine. Affordable methods of predicting neuropathy risk are needed to guide prescribing in countries where some use of stavudine remains an economic necessity. We therefore aimed to identify factors predictive of neuropathy risk before antiretroviral use. METHODS: A total of 294 patients attending clinics in Melbourne, Kuala Lumpur, and Jakarta were enrolled in a cross-sectional neuropathy screening program in 2006. Neuropathy was defined by the presence of symptoms and signs on the AIDS Clinical Trials Group Brief Peripheral Neuropathy Screen. Demographic, laboratory, and treatment details were considered as possible risk factors for neuropathy. The role of patient demographics in predicting stavudine neuropathy were then assessed in 181 patients who reported that they were free of neuropathy symptoms when first prescribed this drug. RESULTS: The prevalence of neuropathy was 42% in Melbourne (n = 100), 19% in Kuala Lumpur (n = 98), and 34% in Jakarta (n = 96). In addition to treatment exposures, increasing age (p = 0.002) and height (p = 0.001) were independently associated with neuropathy. Age and height cutoffs of =170 cm or =40 years predicted neuropathy. Among 181 patients who were asymptomatic before stavudine exposure, the risk of neuropathy following stavudine was 20% in younger, shorter patients, compared with 66% in older, taller individuals. CONCLUSIONS: Stavudine neuropathy risk increases with patient age and height. Prioritizing older and taller patients for alternative agents would be an inexpensive strategy to reduce neuropathy rates in countries where the burden of HIV disease limits treatment options. © 2009 AAN Enterprises, Inc.